2014
DOI: 10.1186/s13620-014-0028-8
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis in dogs: etiology, clinical and histopathological features (11 cases: 2007–2013)

Abstract: BackgroundMyocarditis is a disease caused by numerous etiological factors and characterized by a non-specific course. The only method allowing for precise characterization of inflammatory changes is the histopathological examination of heart muscle specimens. The study was conducted on heart muscle preparations from 11 dogs with ante-mortem diagnosis of cardiac disease. Animals presented with a poor response to an applied treatment or had suspected sudden cardiac death. The heart specimens were taken post-mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 29 publications
2
36
0
3
Order By: Relevance
“…In contrast to humans, no erythema migrans has been observed in dogs (Appel et al 1993), but synovial lesions were significant in infected dogs in all canine experimental studies (Appel et al 1993;Summers et al 2005;Susta et al 2012;Wagner et al 2012). After natural infection, lameness has been described in <5 % of dogs (Levy and Magnarelli 1992;McKenna et al 1995;Hovius et al 2000;Chou et al 2006;Littman et al 2006), less than 1 -2 % show kidney disease (Dambach et al 1997;Chou et al 2006;Littman 2013), and the very rare cases with cardiac (Chou et al 2006;Agudelo et al 2011;Janus et al 2014) and neurological (McKenna et al 1995) involvement are assumed rather than documented. No association was found between exposure to either Borrelia species (or A. phagocytophilum) and neurological signs or inflammatory CNS disease in retrospective and prospective studies (Jäderlund et al 2007(Jäderlund et al , 2009, which have been subsequently confirmed by experimental infection (Krimer et al 2011).…”
Section: Borrelia Vaccinationmentioning
confidence: 66%
“…In contrast to humans, no erythema migrans has been observed in dogs (Appel et al 1993), but synovial lesions were significant in infected dogs in all canine experimental studies (Appel et al 1993;Summers et al 2005;Susta et al 2012;Wagner et al 2012). After natural infection, lameness has been described in <5 % of dogs (Levy and Magnarelli 1992;McKenna et al 1995;Hovius et al 2000;Chou et al 2006;Littman et al 2006), less than 1 -2 % show kidney disease (Dambach et al 1997;Chou et al 2006;Littman 2013), and the very rare cases with cardiac (Chou et al 2006;Agudelo et al 2011;Janus et al 2014) and neurological (McKenna et al 1995) involvement are assumed rather than documented. No association was found between exposure to either Borrelia species (or A. phagocytophilum) and neurological signs or inflammatory CNS disease in retrospective and prospective studies (Jäderlund et al 2007(Jäderlund et al , 2009, which have been subsequently confirmed by experimental infection (Krimer et al 2011).…”
Section: Borrelia Vaccinationmentioning
confidence: 66%
“…All dogs were fasted overnight and determined to be euthyroid with no evidence of systemic illness on routine laboratory diagnostics including CBC, serum biochemical profile, urinalysis, and serum total T4 concentration. Past infectious diseases, such as ehrlichiosis and Lyme disease, and immune‐mediated disease were not evaluated but dogs with a history of infectious or immune‐mediated disease were excluded . Body condition was assessed by a validated 9‐point scale in which ideal body condition was defined as a body condition score (BCS) of 4 or 5 .…”
Section: Methodsmentioning
confidence: 99%
“…Past infectious diseases, such as ehrlichiosis and Lyme disease, and immune-mediated disease were not evaluated but dogs with a history of infectious or immune-mediated disease were excluded. 32 Body condition was assessed by a validated 9-point scale in which ideal body condition was defined as a body condition score (BCS) of 4 or 5. 33,34 Dogs with normal BCSs of 4 and 5 were allocated to the ideal weight group and dogs with BCSs of 6, 7, 8, and 9 were allocated to the obese group.…”
Section: Animalsmentioning
confidence: 99%
“…Staphylococcus, Streptococcus, Citrobacter, Bartonella, Borrelia), fungal agents (i.e. Coccidioides, Cryptococcus, Aspergillus), helminthes (Toxocara), and non-infectious factors such as autoimmune reactions, toxins, trauma, heat stroke, and hemodynamic shock [6].…”
Section: Discussionmentioning
confidence: 99%
“…Through PCR analysis, we tested the most common etiologic agents reported to cause myocarditis in dogs [6] and all viruses resulted to be negative. Others rare non-viral agents causing myocarditis in dogs could not be tested with molecular biology due to financial constrains.…”
Section: Discussionmentioning
confidence: 99%